Evaluation of environmental damage due to accident radionuclide thermoelectric generator - Голяткіна, Т.М.; Тихенко, О.М.; Криворотько, В.М.; Кутлахмедов, Ю.О. (Proceedings of National Aviation University, 2007)
Modeling results of hypothetic emergency situation on radionuclides thermoelectrical generator are presented. The box model method was used. The dynamics of behavior and migration for radionuclides flows in ecosystem during one year after the accident were assessed. Ecological damage was calculated.